Managing organizations : current issues - Clegg, Stewart; Hardy, Cynthia, 1956-; Nord, Walter R. (Sage Publications, 1999)
Summary: This text addresses key topics such as leadership and decision making and innovation in organizations alongside such themes as diversity, globalization and ecology.